Tourism Resources And Development Strategies In Cuddalore District - Jayasri, A.; Karthikeyan, K. (Journal of Neonatal Surgery, 2025)
Tourism in Cuddalore District reflects a varied spatial and thematic composition shaped by coastal ecology, riverine landscapes, religious centres, colonial-era sites, and locally embedded cultural practices. The district accommodates beach-based locations along the Bay of Bengal, pilgrimage centres associated with Saiva and Vaishnava traditions, inland wetlands, and heritage structures linked to European trading networks. Despite this range, tourism activity remains uneven, with limited infrastructure integration, seasonal concentration, and modest linkage to local livelihoods. Emphasis is placed on resource classification, accessibility, institutional coordination, environmental sensitivity, and community participation. The analysis foregrounds planning-oriented strategies such as destination clustering, heritage conservation frameworks, coastal regulation alignment, and skill-oriented employment generation. Such an approach situates tourism as a supplementary regional development instrument rather than a standalone growth sector, requiring policy coherence, local governance capacity, and sustainability-oriented investment..